High-level intra- and extra-cellular production of d-psicose 3-epimerase via a modified xylose-inducible expression system in Bacillus subtilis. (1st November 2016) - Chen, Jingqi; Zhu, Yueming; Fu, Gang; Song, Yafeng; Jin, Zhaoxia; Sun, Yuanxia; Zhang, Dawei
Abstract: d -Psicose 3-epimerase (DPEase) converts d -fructose into d -psicose which exists in nature in limited quantities and has key physiological functions. In this study, RDPE (DPEase from Ruminococcus sp. 5_1_39BFAA) was successfully constitutively expressed in Bacillus subtilis, which is the first report of its kind. Three sugar-inducible promoters were compared, and the xylose-inducible promoter P xylA was proved to be the most efficient for RDPE production. Based on the analysis of the inducer concentration and RDPE expression, we surmised that there was an extremely close correlation between the intracellular RDPE expression and xylose accumulation level. Subsequently, after the metabolic pathway of xylose was blocked by deletion of xylAB, the intra- and extra-cellular RDPE expression was significantly enhanced. Meanwhile, the optimal xylose induction concentration was reduced from 4.0 to 0.5 %. Eventually, the secretion level of RDPE reached 95 U/mL and 2.6 g/L in a 7.5-L fermentor with the fed-batch fermentation, which is the highest production of DPEase by a microbe to date.